2011
DOI: 10.1007/s00261-011-9763-4
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound: a new method for TIPS follow-up

Abstract: CEUS allows direct visualization of intra-prosthetic flow, with a qualitative and anatomic study, in addition to the Doppler examination. This is a new, simple, and effective technique for TIPS follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…On the other hand, CEUS is characterized by some limitations that also apply to the unenhanced conventional technique. For example, attenuation because of the deep position of the stent, and obesity and bowel gas can affect the imaging [24]. However, in our experience, as long as adequate intestinal preparation is accomplished, CEUS is easy to perform, and good image quality can be obtained.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…On the other hand, CEUS is characterized by some limitations that also apply to the unenhanced conventional technique. For example, attenuation because of the deep position of the stent, and obesity and bowel gas can affect the imaging [24]. However, in our experience, as long as adequate intestinal preparation is accomplished, CEUS is easy to perform, and good image quality can be obtained.…”
Section: Discussionmentioning
confidence: 87%
“…With the use of contrast agents, CEUS overcomes angular dependence and the shortcoming of DUS by increasing the signal-to-noise ratio [24]. Blood ow is easy to depict with contrast material, and the visualization of the ISR is more intuitive by contrast agent lling defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With covered devices, the hepatic venous outflow of the TIPS tract is the major site of subsequent obstruction [14], [28]. Although the clinical application of covered stent-grafts has improved the primary patency rates after TIPS procedures [5], [6], the one-year patency was reported to be still limited, even as low as 38% [29].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also demonstrated that the hepatic venous outflow is the primary site of stenosis when covered stent are used to construct the TIPS [13], [14]. To overcome this problem, the current practice is to extend the outflow ends of the stent-grafts from the TIPS tract into inferior vena cava (IVC).…”
Section: Introductionmentioning
confidence: 99%